Advances in animal models of cognitive impairment secondary to coronary heart disease - Qing WANG; Feng-Lan LIU; Shi-Han XU; Yan-Fei LIU; Yue LIU; Feng-Qin XU (Yixue xinzhi zazhi)
Coronary heart disease and cognitive impairment are both major diseases harmful to human health. A large number of studies have shown that coronary heart disease increases the risk of cognitive impairment in patients with the disease. It is of great clinical significance to explore the mechanism, prevention and treatment of such comorbidities. Research on the pathogenesis and treat-ment of cognitive impairment secondary to coronary heart disease has currently become a hot topic. It is critical to build and select an appropriate animal model to successfully carry out relevant experimental research. This paper systematically summarizes the methods of constructing animal models of cognitive impairment secondary to coronary heart disease. It also combs the commonly used detection indicators and evaluation methods in order to provide a reference for the experimental study of cognitive impair-ment secondary to coronary heart disease.